Design of Mathematical Module Development Design of Learning Model Number Head Together to Improve Students Learning and Study Result - Sari, Ika Putri Astriyana; Suparman, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
The ability of collaboration is one of the important competencies that students must possess in learning 21st-century mathematics. Students who do not have the ability to cooperate will not get experience, can’t develop themselves, and don’t get new skills. This research has two objectives. First, this study is to analyze the needs of modules that are appropriate to the characteristics of students. Second, this research is to design modules that can enhance the ability of collaboration. This research is a research using Design Research Model which consists of two stages, namely the preliminary stage and the formative evaluation stage. The subjects of this study were teachers and students of class VII. Data collection instruments use validation sheets, interview guidelines, and questionnaires. Validation sheets are given to experts to obtain criticism and suggestions related to the material. Interview guidelines are used to obtain information on the condition of schools, students, and the media used in schools. The questionnaire is given to teachers and students to get criticisms and suggestions related to the media. Data analyzed using descriptive analysis. This study provides results that students and teachers need modules that are able to improve the ability of collaboration between students. This study concludes that the development of Number Head Together learning models assisted by mathematical modules to improve student collaboration on social arithmetic material needs to be developed.